Loss of BCAT1 Expression is a Sensitive Marker for IDH-Mutant Diffuse Glioma. Issue 3 (3rd August 2018) - Chen, Yen-Ying; Ho, Hsiang-Ling; Lin, Shih-Chieh; Hsu, Chih-Yi; Ho, Donald Ming-Tak
Abstract: BACKGROUND: IDH mutation is an important prognostic factor of diffuse astrocytomas. Although the majority of IDH mutations could be identified by immunohistochemical (IHC) stain for R132H-mutant IDH1, DNA sequencing would be required for IHC negative cases to determine their IDH mutation status. This approach is not cost-effective for tumors with low IDH mutation rates. OBJECTIVE: To investigate whether BCAT1 could be used as a surrogate marker for IDH mutations, because BCAT1 is an enzyme related to IDH genes. METHODS: A group of 120 anaplastic astrocytomas were immunostained for BCAT1, ATRX, and R132H-mutant IDH1. Staining results correlated with the results of DNA sequencing of IDH1/IDH2 . RESULTS: DNA sequencing showed IDH1/2 mutations in 50.8% of cases of which 73.8% had IDH1 R132H mutation. Several IDH1 noncodon 132 mutations, ie, G97D, S122N, G123E, I130K, and G131S, which had uncertain prognostic significance, were identified. IHC stain for R132H-mutant IDH1 identified 93.3% of IDH1 R132H mutations and 70.5% of all IDH mutations. BCAT1 loss was seen in 65.8% of cases, its sensitivity to identify IDH mutations was 96.7%. The sensitivity reached 100% for IDH1 codon 132 and IDH2 codon 172 mutations. CONCLUSION: Positive BCAT1 stain could be used to exclude diffuse gliomas with IDH1 codon 132 and IDH2 codon 172 mutations. Selecting cases with negative BCAT1 and R132H-mutant IDH1 staining for DNA sequencing of IDH1/2 genes could improve the cost-effectiveness of detecting IDH mutations particularly in tumors with low IDH mutation rates, and confine the need of 1p/19q assay in IDH-mutant tumors.